What are Your Key Take Home Messages at the Time of the Program Launch? - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Interview with CGIAR Climate Program Director Bruce Campbell. Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya